13. Sinergitas Mahasiswa KKN UIN Bandung Bersama Masyarakat Desa Cisondari - Schatzi Aprilluna Nur’aini; Nurhadi Ikhsan; Wida Alifa; Wida Alifa (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Community Service Learning (KKN) in Indonesia facilitates students to apply their knowledge for the benefit of the community. Group KKN 153 Cisondari focuses on madrasah, an Islamic educational institution in Cisondari Village. Through this program, students are taught religious materials, Arabic and English at Madrasah Yayasan Nurul Bayan Al-Badawi. Using methods such as surveys, planning, collaboration with religious teachers, and evaluation, the group aims to enhance the quality of education. Challenges like student discipline and limited facilities were encountered, but innovative solutions were implemented. This highlights the relevance of community service in education and community empowerment.